Usage of Interactive Methods in Organization of Individual Work of Students in Ukrainian Literature - Hlotova, Iryna (Pedagogical Discourse, 2014)
In article the use of interactive methods in the organization of studends’ individual work in Ukrainian literature has been analyzed. Basics of the organization of training are studied in the interactive mode. Group interactive methods, which according to the author, are the best option of the organization of educational process at which the student is the subject of cognitive activity, have been singled out and analyzed. It is established that the use of such technologies not only promotes effective development of the student, but also the teacher, gives the chance for professional growth, for changes of himself or herself, for training together with students.